Metal‐HisTag coordination for remote loading of very small quantities of biomacromolecules into PLGA microspheres. Issue 2 (17th February 2022) - Albert, Jason; Chang, Rae Sung; Garcia, George A.; Schwendeman, Steven P.
Abstract: Challenges to discovery and preclinical development of long‐acting release systems for protein therapeutics include protein instability, use of organic solvents during encapsulation, specialized equipment and personnel, and high costs of proteins. We sought to overcome these issues by combining remote‐loading self‐healing encapsulation with binding HisTag protein to transition metal ions. Porous, drug‐free self‐healing microspheres of copolymers of lactic and glycolic acids with high molecular weight dextran sulfate and immobilized divalent transition metal (M 2+ ) ions were placed in the presence of proteins with or without HisTags to bind the protein in the pores of the polymer before healing the surface pores with modest temperature. Using human serum albumin, insulin‐like growth factor 1, and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), encapsulated efficiencies of immunoreactive protein relative to nonencapsulation protein solutions increased from ~41%, ~23%, and ~9%, respectively, without Zn 2+ and HisTags to ~100%, ~83%, and ~75% with Zn 2+ and HisTags. These three proteins were continuously released in immunoreactive form over seven to ten weeks to 73%–100% complete release, and GM‐CSF showed bioactivity >95% relative to immunoreactive protein throughout the release interval. Increased encapsulation efficiencies were also found with other divalent transition metals ions (Co 2+, Cu 2+, Ni 2+, and Zn 2+ ), but not with Ca 2+ . Ethylenediaminetetraacetic acid was found to interfere with this process, reverting encapsulation efficiency back to Zn 2+ ‐free levels. These results indicate that M 2+ ‐immobilized self‐healing microspheres can be prepared for simple and efficient encapsulation by simple mixing in aqueous solutions. These formulations provide slow and continuous release of immunoreactive proteins of diverse types by using a amount of protein (e.g., <10 μg), which may be highly useful in the discovery and early preclinical development phase of new protein active pharmaceutical ingredients, allowing for improved translation to further development of potent proteins for local delivery.